1998
DOI: 10.1089/acm.1998.4.1-87
|View full text |Cite
|
Sign up to set email alerts
|

Some Biological Actions of Alkylglycerols from Shark Liver Oil

Abstract: Shark liver oil has been used for over 40 years as both a therapeutic and preventive agent. The active ingredients in shark liver oil have been found to be a group of ether-linked glycerols known as alkylglycerols. Initial clinical use was for treating leukemias, and later to prevent radiation sickness from cancer x-ray therapy. Studies over the last 30 years have shown that alkylglycerols are multifunctional. The level of natural alkylglycerols rises within tumor cells, apparently in an effort to control cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Alkylglycerols, alkylglycerophospholipids and their derivatives, commonly known as ether lipids, have been the subject of much attention because of their special physiological functions in humans [1,2]. Ether lipids have been used in the therapy of cancer [3], since they are potent antineoplastic agents which inhibit growth, show antimetastatic activity and induce differentiation and apoptosis in cancer cells [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Alkylglycerols, alkylglycerophospholipids and their derivatives, commonly known as ether lipids, have been the subject of much attention because of their special physiological functions in humans [1,2]. Ether lipids have been used in the therapy of cancer [3], since they are potent antineoplastic agents which inhibit growth, show antimetastatic activity and induce differentiation and apoptosis in cancer cells [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has specifi c function in the cholesterol transport pathways. It reduces radiation damage, suppress tumor growth, increase haemopoesis, accelerate wound healing, prevent cataract etc 7 . It is found to be a major constituent of synaptic vesicle membranes, in alveolar surfactants, indicating involvement in endogenous antioxidant capacity it is used in human medicines 3,7 .…”
Section: Introductionmentioning
confidence: 99%
“…It reduces radiation damage, suppress tumor growth, increase haemopoesis, accelerate wound healing, prevent cataract etc 7 . It is found to be a major constituent of synaptic vesicle membranes, in alveolar surfactants, indicating involvement in endogenous antioxidant capacity it is used in human medicines 3,7 . It has been reported that dietary intake of ether glycerolipids helps in the synthesize of membrane plasmalogen in most tissues and there by increase the biological functions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Shark liver oil (SLO) has been traditionally used in Scandinavian medicine for the treatment of general debility and several other specific applications such as wound healing and the treatment of the respiratory and alimentary tracts (Pugliese et al 1998;Krotkiewski et al 2003). SLO is a rich source of a group of ether-linked glycerols known as alkylglycerols, which are found to a lesser extent in haematopoietic organs (e.g., bone marrow, spleen, liver), lymphatic tissues, blood and maternal milk (Hallgren and Larsson 1962).…”
Section: Introductionmentioning
confidence: 99%